Early Stages of Obesity-related Heart Failure Are Associated with Natriuretic Peptide Deficiency and an Overall Lack of Neurohormonal Activation: The Copenhagen Heart Failure Risk Study. Issue 1 (25th March 2020) - Gaborit, Freja Stoltze; Kistorp, Caroline; Kümler, Thomas; Hassager, Christian; Tønder, Niels; Iversen, Kasper; Kamstrup, Pia R.; Faber, Jens; Køber, Lars; Schou, Morten
Objective: This study evaluated the associations between the natriuretic peptide activity and the neurohormonal response in non-obese and obese outpatients with and without heart failure (HF). Background: Obesity-related HF may be a distinct subtype of HF. Obesity is associated with lower plasma concentrations of natriuretic peptides. The associations between obesity and neurohormonal activation estimated by mid-regional pro-adrenomedullin (MR-proADM) and copeptin in patients with HF is not elucidated. Methods: This prospective cohort-study included 392 outpatients ≥60years, plus ≥1 risk-factor(-s) for HF (hypertension, ischemic heart disease, atrial fibrillation, diabetes, chronic kidney disease), and without known HF. Patients were categorized 'non-obese' BMI = 18.5–29.9 kg/m 2 (n = 273) and 'obese' BMI ≥ 30 kg/m 2 (n = 119). The diagnosis of HF required signs, symptoms, and abnormal echocardiography. NT-proBNP, MR-proANP, MR-proADM, and copeptin were analyzed. Results: Obese patients were younger, had a higher prevalence of diabetes and chronic kidney disease, but a lower prevalence of atrial fibrillation. A total of 39 (14.3%) non-obese and 26 (21.8%) obese patients were diagnosed with HF. In obese patients, HF was not associated with higher plasma concentrations of NT-proBNP (Estimate: 0.063; 95%CI: –0.037–1.300; P = 0.064), MR-proANP (Estimate: 0.207; 95%CI: –0.101–0.515; P = 0.187), MR-proADM (Estimate: 0.112; 95%CI: –0.047–0.271; P = 0.168), or copeptin (Estimate: 0.093; 95%CI: –0.333–0.518; P = 0.669). Additionally, obese patients with HF had lower plasma concentrations of NT-proBNP (Estimate: –0.998; 95%CI: –1.778–0.218; P = 0.012), and MR-proANP (Estimate: –0.488; 95%CI: –0.845–0.132; P = 0.007) compared to non-obese patients with HF, whereas plasma concentrations of MR-proADM (Estimate: 0.066; 95%CI: –0.119–0.250; P = 0.484) and copeptin (Estimate: 0.140; 95%CI: –0.354–0.633; P = 0.578) were comparable. Conclusions: Patients with obesity-related HF have natriuretic peptide deficiency and lack of increased plasma concentrations of MR-proADM and copeptin suggesting that patients with obesity-related HF have a blunted overall neurohormonal activity.